2007
DOI: 10.1158/1055-9965.epi-06-0615
|View full text |Cite
|
Sign up to set email alerts
|

Differential Induction in Telomerase Activity among Bladder Cancer Patients and Controls on γ-Radiation

Abstract: Expression of telomerase is one of the hallmarks of tumor cells and has been used as a diagnostic biomarker and a therapeutic target in cancer. Novel findings have shown that telomerase activation in normal human epithelial cells may affect expression of several cancer-related genes, such as growth-related genes and c-myc gene, suggesting a possible role of telomerase in tumor initiation. Therefore, we hypothesized that individuals who are sensitive to mutagen challenge in terms of induced telomerase activity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 20 publications
1
7
0
Order By: Relevance
“…In contrast, an up-regulation of TA after irradiation was reported in peripheral blood mononuclear cells after mitogen stimulation and in hematopoietic cell lines (30). Interestingly, the group of Xing et al found that lymphocytes from normal controls did not activate telomerase after ex vivo irradiation, whereas lymphocytes isolated from patients with bladder and lung cancers exhibited telomerase activation (17). The apparent difference in response to irradiation of normal and malignant cells may reflect different signaling pathways, such as differential activation of the PI3K/Akt pathway in response to irradiation between tumor and primary endothelial cells (31).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In contrast, an up-regulation of TA after irradiation was reported in peripheral blood mononuclear cells after mitogen stimulation and in hematopoietic cell lines (30). Interestingly, the group of Xing et al found that lymphocytes from normal controls did not activate telomerase after ex vivo irradiation, whereas lymphocytes isolated from patients with bladder and lung cancers exhibited telomerase activation (17). The apparent difference in response to irradiation of normal and malignant cells may reflect different signaling pathways, such as differential activation of the PI3K/Akt pathway in response to irradiation between tumor and primary endothelial cells (31).…”
Section: Discussionmentioning
confidence: 97%
“…Data regarding the effect of radiation on TA are conflicting. Several reports described upregulation, whereas others showed the opposite (12,13,17). These discrepancies in TA can be attributed to different methodologies such as different cell lines, varying doses of radiation, and different time points assessing its effect.…”
mentioning
confidence: 99%
“…Telomerase activity is critical for chromosomal stability and has been associated with bladder cancer risk (Alvarez and Lokeshwar 2007; Xing et al 2007). TERT1 protein levels are a rate limiting step in telomerase activity and were associated with better survival in a previous study of 132 bladder cancer cases ( P = 0.007) (Ito et al 1998; Mavrommatis et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of telomerase in cancer cells has been shown to impair tumor growth and sensitize cancer cells to radiation treatment, as discussed in Section 2.2.1. IR exposure was shown to up-regulate telomerase in human hematopoietic and cancer cells [183188]. However, this is still a matter of debate, as much conflicting data exists.…”
Section: Telomere Maintenance and The Effects Of Ionizing Radiationmentioning
confidence: 99%